PENGARUH PENERAPAN TERAPI OKUPASI KERAJINAN TANGAN TERHADAP TINGKAT KOGNTIF LANSIA DI PANTI WERDHA BINA BHAKTI SERPONG - Yogie Erlangga Haq; Syiva Annisa Fauziah; Dewa Ayu Sri Saraswati (STIKes IMC Bintaro, 2020)
Changes that occur in the elderly can cause cognitive decline. Cognitive setbacks are setbacks caused by primary degenerative diseases of the central nervous system and are a natural process that can be experienced by all the elderly over time. This study aims to determine the effect of the application of handicraft occupational therapy to the cognitive level of the elderly in the Nursing Home at Bina Bhakti Serpong. The method in this study uses a pre-experimental research design (one group pre-test and post-test design). The population of this study is the elderly who are aged 60 years to 85 years and are still productive as many as 26 respondents. The sampling technique uses quota random sampling. The data collection technique was using a Mini Mental Status Exam (MMSE) cognitive level assessment sheet. In this study the data analysis used is the T-test of Related Test (p <0.05). The analysis results obtained that the cognitive level before (pre-test) occupational therapy is known to the elderly with cognitive levels 24-30 as many as 7 elderly (27%), cognitive status 18-23 as many as 5 elderly (19%), cognitive level 0-17 as many as 14 elderly (54%) and cognitive level after (post test) occupational therapy is known to the elderly with cognitive status 24-30 as many as 11 elderly (42%), cognitive level 18-23 as many as 10 elderly (39%), cognitive status 0-17 as many as 5 elderly (19%). The conclusion of this study is that there is an effect of the application of handicraft occupational therapy to the cognitive level of the elderly in the Nursing Home at Bina Bhakti Serpong. The application of occupational therapy needs to be a therapy that is developed in the elderly to fill the leisure time of the elderly and train the memory of the elderly.